Vem är samen? : En läromedelsanalys av hur samisk kultur och identitet presenteras i Undervisningsmaterial i historia och religion - Bergmann, Jennifer (Religionsvetenskap, 2014)
The aim of this essay is to study how the Sami are presented in four textbooks about religion and history that are used in the schools of the majority culture of Sweden today and one book of ideas asto how a textbook could look like from a Sami's perspective. Its aim is not only to study how the Sami are presented but also to discuss how students who read these books could interpret what it means to be a Sami and what their culture is about. It is also meant to discuss how the Sami identitycould be formed. In order to be able to discuss this the essay uses three different kinds of theories about identity and culture. The analysis showed that there is little information about Sami culture, identity, religion and historypresented in the four textbooks used in schools of the majority culture and that these books seem to want students to think that the Sami are troublemakers but are and should be assimilated into the majority culture.